2003
DOI: 10.1242/jcs.00311
|View full text |Cite
|
Sign up to set email alerts
|

Nucleolar association of pEg7 and XCAP-E, two members ofXenopus laeviscondensin complex in interphase cells

Abstract: Cell cycle dynamics and localization of condensins — multiprotein complexes involved in late stages of mitotic chromosome condensation —were studied in Xenopus laevis XL2 cell line. Western blot analysis of synchronized cells showed that the ratio of levels of both pEg7 and XCAP-E to β-tubulin levels remains almost constant from G1 to M phase. pEg7 and XCAP-E were localized to the mitotic chromosomes and were detected in interphase nuclei. Immunostaining for condensins and nucleolar proteins UBF,fibrillarin an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 66 publications
2
18
0
Order By: Relevance
“…This contrasts with previously published results in which the barr L305 allele was shown to suppress 5F24(25,2) variegation in adult female progeny (Lupo et al 2001) but is nonetheless consistent with more recent findings concerning the lack of any discernible effect of dcap-g mutations on regulation of gene expression by the Fab-7 Polycombgroup response element (Dej et al 2004). However, as the w m4h inversion places the white gene near the bobbed multicopy rDNA array within pericentric heterochromatin, it is possible that the PEV assay performed with w m4h flies may be more sensitive to mutations affecting condensin components if such proteins are enriched at rDNA loci as in other species (Freeman et al 2000;Cabello et al 2001;Bhalla et al 2002;Uzbekov et al 2003;D'Amours et al 2004;Wang et al 2004) and since various condensin proteins in Drosophila have been shown to be enriched at mitotic centromeres (Steffensen et al 2001;Savvidou et al 2005). To evaluate whether the effects of condensin mutations on PEV were specific to particular chromosomal regions, additional crosses were performed between selected alleles and flies carrying transgenic white reporter genes at different chromosomal loci.…”
Section: Mitotic Defects In Gluon and Dcap-g Mutant Embryossupporting
confidence: 90%
“…This contrasts with previously published results in which the barr L305 allele was shown to suppress 5F24(25,2) variegation in adult female progeny (Lupo et al 2001) but is nonetheless consistent with more recent findings concerning the lack of any discernible effect of dcap-g mutations on regulation of gene expression by the Fab-7 Polycombgroup response element (Dej et al 2004). However, as the w m4h inversion places the white gene near the bobbed multicopy rDNA array within pericentric heterochromatin, it is possible that the PEV assay performed with w m4h flies may be more sensitive to mutations affecting condensin components if such proteins are enriched at rDNA loci as in other species (Freeman et al 2000;Cabello et al 2001;Bhalla et al 2002;Uzbekov et al 2003;D'Amours et al 2004;Wang et al 2004) and since various condensin proteins in Drosophila have been shown to be enriched at mitotic centromeres (Steffensen et al 2001;Savvidou et al 2005). To evaluate whether the effects of condensin mutations on PEV were specific to particular chromosomal regions, additional crosses were performed between selected alleles and flies carrying transgenic white reporter genes at different chromosomal loci.…”
Section: Mitotic Defects In Gluon and Dcap-g Mutant Embryossupporting
confidence: 90%
“…Condensin II and I associate with chromosomes in prophase and prometaphase, respectively Based on immunofluorescence (IF) microscopy experiments, condensin I has been reported to be located in the nucleus of interphase cells (Cabello et al, 2001;Uzbekov et al, 2003); however, the complex has also been found to be cytoplasmic (Ball et al, 2002;Cabello et al, 2001;Maeshima and Laemmli, 2003;Schmiesing et al, 2000;Steffensen et al, 2001;Uzbekov et al, 2003). The latter finding was surprising considering the genetic evidence that condensin subunits are required for chromosome condensation in prophase (Hagstrom et al, 2002;Kaitna et al, 2002;Hudson et al, 2003), i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Differential localisation of condensin subunits during interphase in Drosophila suggests that CAP-D2 may be sequestered away from SMCs to regulate activity or may be utilized for a function other than that required of other condensin subunits during interphase. It has recently been shown in Xenopus that CAP-D2 (pEg7) along with SMC2 (XCAP-E) localise in the granular compartment of the nucleolus, suggesting that these subunits may be involved in nucleolar organisation and/or ribosome biogenesis (Uzbekov et al, 2003). In S. cerevisiae, the CAP-D2 orthologue Ycs4 is nuclear during interphase, implicated in suppressing inter-repeat rDNA recombination and required for silencing at the mating-type loci (Bhalla et al, 2002).…”
Section: Discussionmentioning
confidence: 99%